Effect of needle diameter on the viability of equine bone marrow derived mesenchymal stem cells. Issue 5 (22nd March 2017) - Lang, Hayley M.; Schnabel, Lauren V.; Cassano, Jennifer M.; Fortier, Lisa A.
Abstract: Objectives: Mesenchymal stem cells (MSCs) are frequently delivered via needle injection for treatment of musculoskeletal injuries. The purpose of this study was to evaluate the effect of needle diameter on the viability of MSCs. Methods: Equine bone marrow‐derived MSCs from 5 horses were suspended in PBS, and held at room temperature for 7 hours to mimic shipping conditions. Two replicate samples for each needle size (20, 22, 23, or 25‐gauge [ga]) were aspirated into a 3 mL syringe and re‐injected into the holding vial 3 times, to reproduce the resuspension of cells prior to injection in clinical cases. Cells were stained with fluorescein diacetate and propidium iodide to measure viability. Flow cytometry (FC) was performed to compare cell debris and intact cells between groups. Results: MSC viability was higher when cells were passed through a 20‐ga rather than a 25‐ga needle. Cell suspensions passed through a 20‐ga needle contained a larger percentage of intact cells, compared to 25‐ga samples. The percentage of debris present in cell suspensions tended to increase with decreasing needle diameter. Neither horse nor passage had a significant effect on viability. Conclusions: Cell damage is more likely when MSCs are passed through 25‐ga rather than 20‐ga needles. Clinical relevance: Use of needles larger than 25‐ga is recommended to maintain the viability of MSCs injected in horses.